Corporate Social Responsibility and Human Capital Development In Nigeria: Case Study on Guaranty Trust Bank, Gombe State, Nigeria - Bello, Matthew Funsho; Mohammad Aliyu, Rabi; Osungboye, Biola Muhibat (Universitas Airlangga, 2024)
Abstract This research evaluates human capital development and corporate social responsibility (CSR) in Nigeria, using Guaranty Trust Bank Gombe as a case study, covering the period from 2015 to 2020. The study aims to identify the causes of low human capital development in Nigeria and propose solutions to this persistent issue. Three hypotheses guide this study: the impact of CSR, the growth of human capital in the host community, and a combination of both. The methodology includes data from both primary and secondary sources, analyzed using tables, percentages, questionnaires, oral interviews, and basic statistical methods. Findings indicate that the host community has benefited from Guaranty Trust Bank's human capital development initiatives, with many respondents expressing satisfaction and acknowledging the presence of skills acquisition programs. The study recommends that Guaranty Trust Bank adopt a long-term, sustainable approach to its CSR programs, partnering with relevant stakeholders such as government bodies, non-governmental organizations, and community-based groups to maximize resources and skills. Keywords: corporate social responsibility, human capital development, Guaranty Trust Bank, Gombe State, Nigeria Abstrak Penelitian ini mengevaluasi pengembangan sumber daya manusia dan tanggung jawab sosial perusahaan (CSR) di Nigeria, dengan menggunakan studi kasus Guaranty Trust Bank Gombe, yang mencakup periode 2015 hingga 2020. Penelitian ini bertujuan untuk mengidentifikasi penyebab rendahnya pengembangan sumber daya manusia di Nigeria dan mengusulkan solusi untuk masalah yang terus-menerus ini. Ada tiga hipotesis yang memandu penelitian ini: dampak CSR, pertumbuhan sumber daya manusia di komunitas tuan rumah, dan kombinasi keduanya. Metodologinya mencakup data dari sumber primer dan sekunder, dianalisis menggunakan tabel, persentase, kuesioner, wawancara lisan, dan metode statistik dasar. Temuan menunjukkan bahwa masyarakat setempat telah memperoleh manfaat dari inisiatif pengembangan sumber daya manusia Guaranty Trust Bank, dan banyak responden menyatakan kepuasan dan mengakui adanya program perolehan keterampilan. Studi ini merekomendasikan agar Guaranty Trust Bank mengadopsi pendekatan jangka panjang dan berkelanjutan terhadap program CSR-nya, bermitra dengan pemangku kepentingan terkait seperti badan pemerintah, organisasi non-pemerintah, dan kelompok berbasis masyarakat untuk memaksimalkan sumber daya dan keterampilan. Kata kunci: tanggung jawab sosial perusahaan, pengembangan sumber daya manusia, Guaranty Trust Bank, Negara Bagian Gombe, Nigeria.